Антология выдающихся достижений в науке и технике. Часть 29: Первооткрыватели тайн глобальных природных световых явлений - Баранов, Михаил Иванович (НТУ "ХПИ", 2015)
Приведен краткий научно-исторический очерк про раскрытие отечественными и зарубежными учеными-первопроходцами электрофизических и электрохимических тайн ряда природных световых явлений, носящих для человечества глобальный планетарный характер и сопровождающих протекание в околоземном атмосферном пространстве полярного сияния, радуги и фотосинтеза.

Purpose. Scientifically-historical description of features of opening by scientists-discoverers of the world of electrophysics and electrochemical secrets of such natural light phenomena as Aurora Borealis, rainbow and photosynthesis, carrying global planetary character for the habitants of planet Earth. Methodology. Scientific approaches at treatment and systematization of physical knowledges about «solar wind» and sun radiation, causing flowing in the atmosphere of Earth of the indicated light phenomena. Methods of historical method at research of progressive development in the world of basic scientific knowledges about the examined natural light phenomena. Results. Basic information, touching forming of scientific bases of electrophysics and electrochemical processes, flows at a display in the earthly atmosphere of aurora north (south) polaris, primary (second) rainbow and photosynthesis domestic and foreign scientists in the leaves of higher (lower) plants, is resulted. Originality. First in area of history of scientific and technological bases of electrophysics and electrochemical processes, characteristic for aurora polaris, rainbow and photosynthesis in an earthly magnetic sphere and air atmosphere are presented in the short systematized form and historical development. Practical value. Scientific popularization of electrophysics and electrochemical knowledges and distinguished scientific achievements in area of such global for a planet Earth of the natural atmospheric light phenomena as aurora Borealis, rainbow and photosynthesis.
An anthology of the distinguished achievements in science and technique. Part 29: Discoverers of secrets of global natural light phenomena
Keywords: история науки; планета Земля; сияние полярное; радуга; фотосинтез; history; planet Earth; Aurora Borealis; rainbow; photosynthesis